Indonesia Toll Roads: Its Effect on The Trade Routes in ASEAN - Aldi Adista Juliadi; Alya Sophia Oktirellia; Galuh Chisyti Nur Fadhilah; Indira Shaffiyah; Vina Dwiyanti (Universitas Pendidikan Indonesia (UPI), 2023)
The sea toll road is one of a solution that gives a good effect in the trade routes in the future. Indonesia toll road is a program of the Indonesian government that aims to improve connectivity between regions inequitable distribution of goods so that the movement of the economy can be efficient and evenly distributed. In addition to the impact on the Indonesian state, this program has an impact on countries that are close to Indonesia (ASEAN). The purpose of this study is to analyze how the systematics of Indonesia's toll road program and its effects on the trade routes neighboring countries of Indonesia. The method that we used in this study is review analysis. The result of this study is sea toll facilitates commercial access from southern Pacific countries to Eastern Asian countries. The idea of the Sea Toll concept will open up regional access by making two large international hub ports that can serve large commercial ships above 3,000 TEUs or a Panamax vessel class of 6000 TEUs. This study has an impact on the international shipping process through ASEAN trade routes.